(3GdMQH GdEYdGejI aj MQH GdNdjL GdKGdKI eXGgQ h eOGQS (B/s - (3YHjOj, fhGQs ((3GdLRGFQ (B:s (3eWHYI GdeYGQa ,s, 2006)
(3YfOeG UOQ gPG GdcJGH aj WHYJg GdGhdi aj eGj (B2003 (3GjGeG HYO SbhW HZOGO de fcf fJhbY faGPg HSQYI h dYd eG LGA ajg ef edGMXGJ GhdjI Mhd GdMQH GdGYdGejI GdJj QGabJ GdMQH GdYScQjI dG JRGd Gdi Gdjhe hGVMI GdHjGf NGUI ef MjK GdfXQjGJ h GdeOGQS GdGYdGejI GdYQHjI GdJj GSJfJLJgG GdG eXGgQ gPg GdMQH GdGYdGejI JWhQJ Gdi MO eG h GJSYJ QbbYJgG h de JYO ebJUQI Ydi GdGYdGejjf abW Hd ONd gPg GdMQH GdGWQGa GdYScQjI GdeJUGQYI PGJG NGUI GdebGheI GdYQGbjI h JHYgG ef LeGYGJ h HGSJYeGd JcJjcGJ LOjOI aj GdJGKjQ Ydi GdQGj GdYGe GdYGdej (B. (3dcf bHd GdMOjK Yf gPg GdRGhjI jLH Gf fPcQ HGge GdGMOGK GdJj UfYJ VLI GYdGejI YGdejI GKQJ HGdaYd aj eLQjGJ GdGMOGK(B. s
Keywords: (3GdEYdGes; (3MQH GdNdjLs